The Effect of Service Prices and Service Quality on Consumer Satisfaction at PT. Paramita Ban Workshop Cipete, South Jakarta Period 2023 - Fahrezi, Muhamad Rafli; Pasharibu, Veta Lidya Delimah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study is to determine the influence of service price and service quality on consumer satisfaction at the PT Paramita Ban Cipete Workshop in South Jakarta. The method used is quantitative. The sampling technique used saturated sampling and a sample of 98 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, determination coefficients and hypothesis tests. The results of this study are that the price of services has a significant effect on consumer satisfaction with a determination coefficient value of 25.2% and the hypothesis test is obtained t calculation > t table or (4.788 > 1.988). The quality of service did not have a significant effect on consumer satisfaction with a determination coefficient value of 74.8% and the hypothesis test was obtained by calculating t < t table or (1,616 < 1,988). Service price and service quality simultaneously have a significant effect on consumer satisfaction with the regression equation Y = 19,999 + 0.414 (X1) Y = 19,999 + 0.134 (X2). The value of the determination coefficient was 25.2% while the remaining 74.8% was influenced by other factors. The hypothesis test obtained the F value calculated > F table or (17.764 > 3.094).